Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M208 - Peter Brandt; Rainer Kiko; Anne-Cathrin Wölfl; Mia Schumacher (PANGAEA, 2025)
Raw multibeam bathymetry data were collected aboard RV METEOR during cruise M208 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 14.02.2025 - 17.03.2025 from Mindelo (Cape Verde) – Mindelo (Cape Verde) in the Mid-Atlantic. M208 was an interdisciplinary expedition focusing on upwelling in the tropical Northeast Atlantic. The main topics included the physical forcing of upwelling, its role in biological production and plankton communities, associated chemical cycles, and the resulting downward carbon export. Additionally, the cruise investigated atmospheric forcing, the input of Saharan dust, and its significance for nitrogen fixation and biological productivity. The research conducted during M208 contributed to the Heisenberg Project IOChange and the Program-Oriented Research (POF) of GEOMAR. Furthermore, the expedition served as a preparatory campaign for the FUTURO Project (The Future West African Upwelling System), referred to as FUTUROpre. Data were recorded within the EEZs of Cape Verde, Mauritania, Senegal, Gambia, Guinea-Bissau. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition was done by GEOMAR Helmholtz Centre for Ocean Research, provision of the data is supported by the DAM Underway Project and published according to the FAIR principles.